ANALISA DESAIN ILUSTRASI BUKU CERITA ANAK TEMA SAINS BIOLOGI BERJUDUL “LASKAR BAKTERI BAIK” - Udhi Marsudi; Jovita Nanda (Narada : Jurnal Desain dan Seni, 2020)
In addition to school textbooks, children's storybooks can also be a source of additional knowledge for children. From children's storybooks, the information in the form of knowledge and moral messages can be conveyed. Certainly, the role of visuals such as illustrations also plays an important role in conveying the message. This analysis was made aiming to understand and study the designs used in children's biology-themed science books especially in the field of illustration. The method used in this research is: Reviewing theories about design and illustration. Observing one of the children's storybooks on the theme of bacterial biology and other children's storybooks as a comparison.  Interviewing several experts in the field of illustration children's storybook. The desired result of this research is to understand things about the illustration design used in children's storybooks in Indonesia.